Pembuatan Whatsapp BOT Untuk Sistem Informasi Pelayanan Desa Kromong Ngusikan Jombang - Darmawan, Moh faridl; Sujono, Sujono; Santosa, Ady Luthfi; Khasan, Ahmad Fadlul; Surur, Mohammad Misbakhus; Jamaluddukha, Mokhamad; Ardiansyah, Ardiansyah; Basri, Muhammad Faizal (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
This research designs and builds a WhatsApp chatbot as a provider of community service information in Kromong Village, Ngusikan District with the aim of increasing the effectiveness and efficiency of community services. The tool used is WhatsApp Bot using the Service Learning (SL) method/training and a direct approach to residents, the village can provide information that residents need in real-time, answer questions automatically within 24 hours, and residents don't need to go to the village hall. just to ask about the requirements for managing, making, and so on. From the tests carried out using a questionnaire, pretest and posttest results were obtained, namely with a percentage of 13.33% (very poor) and 88.33% (very good). This shows that respondents strongly agree that this chatbot is capable of being an effective and efficient provider of public service information